Enhancing precision medicine through clinical mass spectrometry platform. Issue 1 (31st December 2022) - Hristova, Julieta; Svinarov, Dobrin
Abstract: There is an extraordinary flood of new technologies in medicine nowadays. Sophisticated diagnostics based on genome assays, mass spectrometry and cell sorting platforms are driving the technological transfer and promote the entrance of individualized patient management in clinical practice. Mass spectrometry (MS) could be viewed as one of the major tools that promote the development of precision medicine (PM), which employs a patient's genotype and phenotype investigation to establish individually tailored drug treatment. While genetic testing allows the physician to choose appropriate medicine, MS assays provide the patient's actual phenotype, with all of the environmental, pharmacological and pathological variables. Therefore, MS is an essential technology for personalized patient management, and high-resolution MS systems are employed to resolve challenging analytical demands. The great technological advance of MS resulted in the introduction of methods with unprecedented identification power, extreme sensitivity, specificity and extended linearity range, which are simpler to use in the medical laboratories, and are based on the current reference analytical principles. Further, the ability to perform panel profiling with simultaneous measurement of bioactive compounds, their precursors and metabolites in a single sample, enormously amplifies the informative value of results, with ultimate improvement of patient care. Typical examples include newborn screening, therapeutic drug management, toxicology, endocrinology, microbiology, clinical omics assays and others. It should be specially emphasized that clinical MS integrates chemical and anatomical pathology: MS imaging and iKnife-MS guidance in surgery, although still in the research phase, open new horizons for personalized treatment and individualized patient care.